Practical solutions for making models indispensable in conservation decision‐making. Issue 5 (6th May 2013) - Addison, Prue F. E.; Rumpff, Libby; Bau, S. Sana; Carey, Janet M.; Chee, Yung En; Jarrad, Frith C.; McBride, Marissa F.; Burgman, Mark A.; Yemshanov, Denys
Abstract Aim Decision‐making for conservation management often involves evaluating risks in the face of environmental uncertainty. Models support decision‐making by (1) synthesizing available knowledge in a systematic, rational and transparent way and (2) providing a platform for exploring and resolving uncertainty about the consequences of management decisions. Despite their benefits, models are still not used in many conservation decision‐making contexts. In this article, we provide evidence of common objections to the use of models in environmental decision‐making. In response, we present a series of practical solutions for modellers to help improve the effectiveness and relevance of their work in conservation decision‐making. Location Global review. Methods We reviewed scientific and grey literature for evidence of common objections to the use of models in conservation decision‐making. We present a set of practical solutions based on theory, empirical evidence and best‐practice examples to help modellers substantively address these objections. Results We recommend using a structured decision‐making framework to guide good modelling practice in decision‐making and highlight a variety of modelling techniques that can be used to support the process. We emphasize the importance of participatory decision‐making to improve the knowledge‐base and social acceptance of decisions and to facilitate better conservation outcomes. Improving communication and building trust are key to successfully engaging participants, and we suggest some practical solutions to help modellers develop these skills. Main conclusions If implemented, we believe these practical solutions could help broaden the use of models, forging deeper and more appropriate linkages between science and management for the improvement of conservation decision‐making.